Internalization of Spiritual Values in Early Childhood Using the Prophet's Storytelling Method - Hambali Hambali; Zakiyah BZ; Zaenol Fajri; Siska Mudrika; Nora Andawiyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Children can grow and develop, both physically and spiritually, from birth. This study aims to discover the absorption of spiritual ideals in early childhood by using the prophet's story approach with the storytelling method. This qualitative research uses interviews, observation, and documentation. The results showed that the first stage in applying the prophet's storytelling method and internalizing spiritual values for early childhood was to analyze the learning process that contained spiritual values in early childhood through the storytelling method. Second, make learning strategies. Third, with a narrative approach to the story of the prophet, learning to instill spiritual principles is carried out in a practical, engaging, and efficient manner. Fourth, evaluation of implementation as feedback for improving the quality of learning. Fifth, applying the prophet's storytelling approach in early infancy provides knowledge and attitudes about worship habits, obedience, and grateful behavior in daily life.